A Dıfferent Perspectıve on “the Challenge of the Qur’an” - Sandal, Halil Hilmi (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The Quranic challenge (Tehaddi) has traditionally been interpreted through linguistic excellence, rhetorical beauty, and semantic depth. However, the visual and structural organisation of the Quranic text has received relatively limited scholarly attention as a potential dimension of its inimitability. Objective: This study aims to explore whether the symmetric and ordered visual structures found across different Mushaf writing traditions offer an additional perspective on the Quranic challenge. Method: The research employs visual symmetry analysis on three Mushaf models: the Alifi Mushaf (K1), the Husrev Mushaf (K2), and the Hunsari Mushaf (K3). Sample pages from Surah Al-Baqarah, verses 164–247, were examined to identify recurring structural patterns. As a comparative, anecdotal test, the literary text A Tale of Two Cities by Charles Dickens was analysed to assess whether a similar symmetry could be reproduced in non-Quranic texts. Results: The findings reveal consistent multi-layered symmetry across the three Mushaf models: line-initial letter symmetry in the Alifi Mushaf, vertical word alignment in the Husrev Mushaf, and mirror-based page symmetry in the Hunsari Mushaf. These patterns persist across hundreds of pages. Conclusion: The Quran can therefore be viewed not only as a linguistic text but also as a visually structured textual system. Contribution: This study introduces a visual-structural perspective that complements traditional discussions of Quranic inimitability.